2023
DOI: 10.1186/s12887-023-04042-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features of SARS-CoV-2 variants across multiple rounds of pandemic waves in hospitalized children in an Iranian referral hospital

Abstract: Background Since the onset of the COVID-19 pandemic, SARS-CoV-2 has evolved into independent new forms, variants of concern (VOCs). While epidemiological data showed increased transmissibility of VOCs, their impact on clinical outcomes is less clear. This study aimed to investigate the differences between the clinical and laboratory features of children infected with VOCs. Methods This study included all cases with SARS-CoV-2-positive nasopharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Other studies found similar results; one of them showed that during the outbreak of the SARS-CoV-2 Delta variant in Vietnam, the case fatality rate was higher [ 27 ]. Another study which included 87 pediatric cases, infected with Alpha (5.7%), Delta (60.9%), and Omicron (33.3%) variants, showed that severe disease, distress, and myalgia were more frequent in Delta-infected patients [ 28 ]. Zachary and collaborators studied 102315 confirmed COVID-19 cases, of which 20, 770 were infected with the Delta variant, 52, 605 with the Omicron B.1.1.529 variant, and 28, 940 with the Omicron BA.2 subvariants.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found similar results; one of them showed that during the outbreak of the SARS-CoV-2 Delta variant in Vietnam, the case fatality rate was higher [ 27 ]. Another study which included 87 pediatric cases, infected with Alpha (5.7%), Delta (60.9%), and Omicron (33.3%) variants, showed that severe disease, distress, and myalgia were more frequent in Delta-infected patients [ 28 ]. Zachary and collaborators studied 102315 confirmed COVID-19 cases, of which 20, 770 were infected with the Delta variant, 52, 605 with the Omicron B.1.1.529 variant, and 28, 940 with the Omicron BA.2 subvariants.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of the Coronavirus disease 2019 (COVID-19) pandemic, the proportion of confirmed cases among children was relatively low, and children were thought to be rarely affected by SARS-CoV-2 ( Mahmoudi et al, 2020 ; Wu and McGoogan, 2020 ; Mohammadpour et al, 2022 ). Subsequent studies have consistently shown that children and adolescents are susceptible to SARS-CoV-2 infection, however, a large percentage of children are either asymptomatic or mildly symptomatic, and the true incidence of infection is underestimated due to low testing rates in children ( Mahmoudi et al, 2023 ). Despite generally milder symptoms, children with COVID-19 are shown to be at a lower risk of hospitalization and severe complications ( Vosoughi et al, 2022 ; Sedik, 2023 ).…”
Section: Introductionmentioning
confidence: 99%